Statistical physics : an entropic approach - Ford, Ian, 1962- (Chichester, West Sussex, United Kingdom : John Wiley & Sons, 2013)
"This undergraduate textbook provides students with a statistical mechanical foundation to the classical laws of thermodynamics through a comprehensive treatment of the basics of classical thermodynamics, equilibrium statistical mechanics, irreversible thermodynamics, and statistical mechanics of non-equilibrium phenomena. The concept of entropy is studied starting from the ideal gas law, known to every undergraduate. By considering various thermodynamic processes, it then explores the concept's generality. An accessible style enables undergraduates to easily follow the presentation without much prior knowledge. The focus on entropy distinguishes the book from many other treatments of this subject"--
"Focuses from the beginning on entropy as the important quantity and introduces it thoroughly in the context of classical thermodynamics"--
1. Disorder or uncertainty? -- 2. Classical thermodynamics -- 3. Applications of classical thermodynamics -- 4. Core ideas of statistical thermodynamics -- 5. Statistical thermodynamics of a system of harmonic oscillators -- 6. The Boltzmann factor and the canonical partition function -- 7. The grand canonical ensemble and grand partition function -- 8. Statistical models of entropy -- 9. Statistical thermodynamics of the classical ideal gas -- 10. Quantum gases -- 11. Boson gas -- 12. Fermion gas -- 13. Photon gas -- 14. Statistical thermodynamics of interacting particles -- 15. Thermodynamics away from equilibrium -- 16. The dynamics of probability -- 17. Fluctuation relations -- 18. Final remarks.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Statistical thermodynamics -- Textbooks; SCIENCE -- Mechanics -- Dynamics -- Thermodynamics; Statistical thermodynamics; Statistical thermodynamics -- Textbooks; SCIENCE -- Mechanics -- Dynamics -- Thermodynamics; Statistical thermodynamics; Electronic books; Textbooks; Electronic books